MERCÚRIO NA COMUNIDADE PLANCTÔNICA DO RESERVATÓRIO DA USINA HIDRELÉTRICA DE SAMUEL (RO), AMAZÔNIA OCIDENTAL - Nascimento, E. L.; Gomes, J. P. O.; Carvalho, D. P.; Almeida, R.; Bastos, W. R.; Miyai, K. R. (Geochimica Brasiliensis, 2012)